Factors predicting delirium among hospitalized older adults in an urban area, Thailand: A prospective cohort study - Kaveenuntachai, Duangrat; Prueksaanantakal, Naphatthorn; Benyapad, Pirunnapa; Chinpinkleaw, Pratin; Jiojinda, Sirichai (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Delirium is a common but often underrecognized complication in hospitalized older adults. It is associated with poor outcomes, including longer hospital stays, increased mortality, and long-term cognitive decline. While numerous studies have explored factors contributing to delirium, there is a lack of research on the context of older adults in Bangkok, Thailand. Understanding the predictors of delirium is crucial for early detection and prevention, particularly in an urban hospital setting. Objective: This study aimed to determine the incidence rate of delirium and identify factors associated with its development in hospitalized older adults. Methods: A prospective cohort study was conducted in four internal medicine wards of a large urban hospital in Bangkok, Thailand. Data were collected from 168 hospitalized older adults (≥60 years) over a 7-day period following admission. The Confusion Assessment Method (CAM), the Mini-Mental State Examination (TMSE), and the Systemic Inflammatory Response Syndrome (SIRS) scores were used to assess delirium and cognitive impairment. Data were collected between January 2022 and October 2022, and participants were evaluated on Day 1 (24 hours after admission), Day 3, and Day 7 or before discharge. Descriptive statistics and multivariate logistic regression were used to analyze predictors of delirium. Results: The incidence rate of delirium among hospitalized older adults was 20.80%, with 19.00% developing delirium within the first 24-48 hours of admission. Multivariate analysis revealed that cognitive impairment (OR_adj = 7.81, p <0.001), infection (SIRS) (OR_adj = 3.80, p = 0.025), age (OR_adj = 1.09, p = 0.010), and the presence of caregivers prior to admission (OR_adj = 0.11, p = 0.008) were significant predictors of delirium. The model explained 35.30% of the variance in delirium occurrence. Conclusion: This study highlights the high incidence of delirium among hospitalized older adults and identifies key risk factors, including cognitive impairment, infection, age, and the presence of caregivers. Early delirium screening, including the use of the CAM and TMSE, should be integrated into nursing care for delirium prevention. Infection prevention and effective management strategies should also be prioritized to reduce delirium risk.